2000
DOI: 10.1046/j.1537-2995.2000.40121482.x
|View full text |Cite
|
Sign up to set email alerts
|

Primitive human HPCs are better maintained and expanded in vitro at 1 percent oxygen than at 20 percent

Abstract: When cultured at 1-percent O(2) for 7 days in presence of IL-3 and SCF, the CD34+ cells present in apheresis components underwent more cell divisions and better maintained their primitive progenitor cell potential. As suggested by previous results in mice, our data on human cells emphasize the potential interest of cultures at low O(2) tension (1%) for cell therapy protocols aimed at expanding primitive HPCs in autografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
3
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 33 publications
9
105
3
2
Order By: Relevance
“…Previously, Ivanovic et al 21 reported that severe hypoxia (0.9-1% O 2 ) favors the self-renewal of murine and human hematopoietic stem cells. Hypoxia has also been reported to modify proliferation and differentiation of CD34 þ CML cells, 22 although CML-associated oncogene BCR/ABL was shown to induce HIF-1a gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Ivanovic et al 21 reported that severe hypoxia (0.9-1% O 2 ) favors the self-renewal of murine and human hematopoietic stem cells. Hypoxia has also been reported to modify proliferation and differentiation of CD34 þ CML cells, 22 although CML-associated oncogene BCR/ABL was shown to induce HIF-1a gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Cells from six different regions of the Ho gradient were isolated and evaluated for hematopoietic activity in the cobblestone area-forming cell (CAFC) assay. CAFC frequencies at shorter (days [7][8][9][10][11][12][13][14] and longer (days [28][29][30][31][32][33][34][35] times in culture were used to measure relatively mature and primitive hematopoietic cell populations, respectively. As shown in Fig.…”
Section: Distribution Of Different Hematopoietic Subsets Along a Ho Dyementioning
confidence: 99%
“…To date, little is known about the distribution and relationship of hematopoietic cells with respect to blood vessels or blood supply. A number of reports have shown that hematopoiesis can be improved ex-vivo by maintaining the cell cultures at levels of between 1% and 3% O 2 (11)(12)(13) but the relevance of such findings to the in vivo situation is uncertain. Chow et al (14) used mathematical modeling of pO 2 distributions in the bone marrow and speculated that stem cells are located at the region with very low pO 2 levels (almost anoxic) because this prevents oxygen radicals from damaging these important cells.…”
mentioning
confidence: 99%
“…We showed previously that resistance to severe hypoxia defines hierarchical levels within normal hematopoietic populations; in vitro colony-forming cells (CFC) are highly hypoxia-sensitive, as opposed to their progenitors, which are hypoxia-resistant [1][2][3][4][5]. Indeed, severe hypoxia enhances maintenance in vitro of normal stem cells capable of short-term hematopoietic reconstitution (STR-HSC).…”
Section: Introductionmentioning
confidence: 99%
“…In the study reported here, targeted to deepen the characterization of the effects of severe hypoxia on leukemia progenitor and stem cells, we used the murine Friend's erythroleukemia (MEL) cell line to address the question of whether cell subsets characterized by different sensitivity to hypoxia are detectable within a clonal leukemia cell line and whether these differences define the level within the progenitor/ stem cell hierarchy. To identify LSC, we used the Culture Repopulating Ability (CRA) assay, developed in our laboratory [2] and extensively applied [3,5,7] to quantify in vitro normal STR-HSC and later adapted to study their leukemic counterpart [11,12]. We found that the MEL cell line is functionally and metabolically heterogeneous in that it comprises hypoxia-sensitive CFC as well as hypoxia-resistant culture repopulating cells (CRC), which correspond to STR-type LSC.…”
Section: Introductionmentioning
confidence: 99%